Association between Living Kidney Donor Post-Donation Hypertension and Recipient Graft Failure - Holscher, Courtenay M. (Transplantation, 2020)
BACKGROUND: Recipients of kidneys from living donors who subsequently develop ESRD also have higher graft failure, suggesting the two donor kidneys share risk factors that could inform recipient outcomes. Given that donor ESRD is rare, an earlier and more common post-donation outcome could serve as a surrogate to individualize counseling and management for recipients. Hypertension is a frequent event prior to donor ESRD; thus early post-donation hypertension might indicate higher risk of graft failure. METHODS: We studied SRTR data to quantify the association between early post-donation hypertension and recipient graft failure using propensity score-weighted Cox proportional hazards regression. We also examined the association between post-donation systolic blood pressure and graft failure. RESULTS: Of 37,901 recipients, 2.4% had a donor who developed hypertension within 2 years post-donation. Controlling for donor and recipient characteristics, recipients whose donors developed hypertension had no higher risk for graft failure (aHR 1.03, 95% CI 0.85-1.25, p=0.72). This was consistent among subgroups of recipients at higher risk for adverse outcomes due to hyperfiltration: African American recipients (aHR 1.10, 95% CI 0.70-1.73, p=0.68) and those with ESRD caused by hypertension (aHR 1.10, 95% CI 0.65-1.85, p=0.73) or diabetes (aHR 0.80, 95% CI 0.56-1.13, p=0.20). However, graft failure was associated with post-donation systolic blood pressure (per 10 mmHg, aHR 1.05, 95% CI 1.03-1.08, p<0.001). CONCLUSION: Although post-donation systolic blood pressure is associated with graft failure, the reported diagnosis of hypertension as determined by the requirement for blood pressure treatment early post-donation did not portend a higher risk of recipient graft failure in the same way as eventual post-donation ESRD.